Hypoxic liver injury after in- and out-of-hospital cardiac arrest: Risk factors and neurological outcome. (April 2019) - Roedl, Kevin; Spiel, Alexander O.; Nürnberger, Alexander; Horvatits, Thomas; Drolz, Andreas; Hubner, Pia; Warenits, Alexandra-Maria; Sterz, Fritz; Herkner, Harald; Fuhrmann, Valentin
Abstract: Background: Hypoxic liver injury (HLI) is a frequent and life-threatening complication in critically ill patients that occurs in up to ten percent of critically ill patients. However, there is a lack of data on HLI following cardiac arrest and its clinical implications on outcome. Aim of this study was to investigate incidence, outcome and functional outcome of patients with HLI after in-hospital cardiac arrest (IHCA) and out-of-hospital cardiac arrest (OHCA). Methods: We conducted an analysis of a cardiac arrest registry data over a 7-year period. All patients with non-traumatic OHCA and IHCA with return of spontaneous circulation (ROSC) treated at the emergency department of a tertiary care hospital were included in the study. HLI was defined according to established criteria. Predictors of HLI, occurrence, clinical and neurological outcome were assessed using multivariable regression. Results: Out of 1068 patients after IHCA and OHCA with ROSC, 219 (21%) patients developed HLI. Rate of HLI did not differ significantly in IHCA and OHCA patients. Multivariate regression analysis identified time-to-ROSC [OR 1.18, 95% CI (1.01–1.38); p < 0.05], presence of cardiac failure [OR 2.57, 95% CI (1.65–4.01); p < 0.001] and Charlson comorbidity index [OR 0.83, 95% CI (0.72–0.95); p < 0.01] as independent predictors for occurrence of HLI. Good functional outcome was significantly lower in patients suffering from HLI after 28-days (35% vs. 48%, p < 0.001) and 1-year (34% vs. 44%, p < 0.001). Occurrence of HLI was associated with unfavourable neurological outcome [OR 1.74, 95% CI (1.16–2.61); p < 0.01] in multivariate regression analysis. Conclusion: New onset of HLI is a frequent finding after IHCA and OHCA. HLI is associated with increased mortality, unfavourable neurological and overall outcome.